Modelagem matemática como ambiente de aprendizagem de conteúdos geométricos no 7º Ano do ensino fundamental - Sousa, Danielly Barbosa de (2010)
This master research work had as its aims to investigate, apply and analyze a didactical intervention on the teaching of Geometry by using mathematical modeling as a learning environment for taking the group students of the Year 7 difficulties over. The students showed difficulties on the geometrical contents, lack of studying habit and doing work and research in groups. For that, is was elaborated and applied a Didactical Propose evolving interactive activities, having as starting point problem-situations that lead the students to elaborate mathematical modeling to facilitate and to give intuitive support to the processes of teaching and learning Geometry. This research work is presented as a case study, by questionnaire, pre and post-tests, activities and in loco observations, done with students of the Year 7 E of the Municipal Secondary School Irmão Damião, located in the city of Lagoa Seca PB. The students group was composed of twenty two from 12 to 18 years old, as the majority from 13 to 15 years old and most of them leaving in the rural area. The data collection was done in six moments from six categories, including the triangulation technique for verifying the data currency. During the didactical intervention, the students did activities which lead them to construct plan maps and marquises about two classroom (Year 7 E and F) having as theoretical framework the procedure of modeling researched by Biembengut and the explicit of mathematical modeling as learning environment by Barbosa, making possible the intermediation between the new knowledge and the known by the student, according to the Vygotsky socio-constructivist theory. As findings, the research has made explicit the students previous and explored knowledge as well as shown to be the Didactical Propose adequate.